ANALYSIS OF PHARMACY DISTRIBUTION WITH GEOGRAPHIC INFORMATION SYSTEM - Dyani Primasari Sukamdi; Lutfan Lazuardi; Sumarni Sumarni (Faculty of Pharmacy, Universitas Gadjah Mada)
The establishment of new health facilities especially pharmacies are needed to fulfill the community needs on health care facilities. The distribution of pharmacies and public accessibility to the pharmacies are necessary to be considered in building of new pharmacy. This study aimed to assess the distribution and accessibility of pharmacies in the city of Yogyakarta. The number of pharmacies including its location and the number of residents were collected from PD IAI Yogyakarta, Central Bureau of Statistics, and Local Health Department of Yogyakarta. After that, data were synchronized and adapted to the real conditions in the field using GPS. The pharmacy distribution was visualized in the Yogyakarta map, while the accessibility was done by calculating the ratio between the number of pharmacies with a population in each district of Yogyakarta city. The results showed that every pharmacies located in district was concentrated in the border of subdistrict areas, so it was concluded as nonnormal distribution and majority clustered in the border of subdistrict area. The ratio of pharmacies compared to population in the Yogyakarta was at 1: 3967. The highest number of pharmacies were in the Umbulharjo subdistrict (25 pharmacies) with the ratio of 1: 3,284, while the smallest number of pharmacies were at two subdistricts, namely Gondomanan and Ngampilan, with only 3 pharmacies at ratio 1: 4365 and 1: 5467 respectively. The smallest ratio was in Pakualaman subdistrict with 1: 1,561, while the largest ratio found in the subdistrict Mergangsan with 1: 7362. The ratio of pharmacy compared to population showed a good level of public accessibility and met the standard from Health Ministry.Keyword: pharmacy, distribution, accesibility, geographic information system